DASHMM Accelerated Adaptive Fast Multipole Poisson-Boltzmann Solver on Distributed Memory Architecture (Communications in Computational Physics, 2018)
We present DAFMPB (DASHMM-accelerated Adaptive Fast MultipolePoisson-Boltzmann solver) for rapid evaluation of the electrostatic potentials andforces, and total solvation-free energy in biomolecular systems modeled by the linearized Poisson-Boltzmann (LPB) equation. DAFMPB first reformulates the LPB intoa boundary integral equation and then discretizes it using the node-patch scheme [33].It solves the resulting linear system using GMRES, where it adopts the DASHMM library [14] to accelerate the matrix-vector multiplication in each iteration. DASHMMis built on top of a global address space allowing the user of DAFMPB to operate onboth shared and distributed memory computers with modification of their code. Thispaper is a brief summary of the program, including the algorithm, implementation,installation and usage.